From Ideological to Aesthetic: a Meeting With the Two “Turismos”, From Carlos de Oliveira - Gama, Chimena Barros da (ITINERÁRIOS – Revue de Littérature, 2009)
To comprehend Carlos Oliveira real participation in the Portuguese Neorealismo, it is important to investigate the work published in 1942, in the collection “Novo Cancioneiro, Turismo”. The book, however, was entirely rewritten by the author, to be published years later in his Completed Works. This fact proposed the challenge of comparing both “Turismos”, and comprehending the implications of those changes. The following text is an attempt (not completed due to the editorial nature) to look into the versions of some author’s poems with the purpose to verify what remains and what has been expunged in the process of rewriting, as well as the motivations and consequences in aestheticals terms.